PRODUCTION OF A NOVEL FRUIT-YOGHURT USING DRAGON FRUIT (HYLOCEREUS UNDATUS L.) - Jayasinghe, Oshadi; Fernando, Sumali; Jayamanne, Vijith; Hettiarachchi, Deepika (European Scientific Journal, ESJ, 2015)
Dragon fruit (hylocereus undatus l.), which is rich in vitamin c, fiber and natural antioxidants, is one of the most popular commercial fruits available in sri lanka. However, dragon fruit is still an underutilized fruit in sri lanka as its high price and exotic taste don’t warrant consumption of the fruit by average sri lankan consumers. The present study investigated the possibility of developing a novel fruit-yoghurt incorporated with white dragon fruit and evaluated its eating quality parameters. An initial survey was conducted to find out the consumer preference for value-added dragon fruit products in Sri Lanka. Pasteurized dragon fruit juice enriched yoghurt (5%, 7.5%, 10%, 12.5% and 15%; w/w) were prepared with the suitable concentrations of sugar and gelatin and sensory properties, ph, titratable acidity, total solid, fat, solid-non-fat (snf) and microbiological properties of the product were determined. Sensory results were analyzed by kruskalwallis non-parametric one way anova method using statistix software (ver 2.0) for windows. Survey results showed that 90% of individuals were eagerly waiting for the new product from dragon fruit in the near future. Sugar (10%), gelatin (0.8%) and dragon fruit juice (10%; w/w) added yoghurt mix was selected as the best product considering its highest mean rank values recorded for sensory properties. The titratable acidity and ph of the developed product during the storage period ranged from 0.8 to 1.0 % and 4.08 to 3.9, respectively. Yeast and mould count did not exceed the sri lanka standards institute (slsi) recommended values during the 15-day storage period. It can be concluded that dragon fruit can be successfully used to develop a fruit-yoghurt with improved sensory and nutritive properties.